Bronchopulmonary dysplasia: A review of the pulmonary sequelae in the post‐surfactant era. (8th April 2020) - Haggie, Stuart; Robinson, Paul; Selvadurai, Hiran; Fitzgerald, Dominic A
Abstract : We describe the respiratory complications of bronchopulmonary dysplasia (BPD) in childhood and adolescence. The pathophysiology of bronchopulmonary dysplasia has evolved in the era of modern neonatal intensive care. In this review, we aim to summarise the contemporary evidence base and describe the common respiratory morbidities related to BPD including; home oxygen therapy, rehospitalisation, asthma and exercise limitation.